Keystone with Greek woman face - Ghosh, Ayan (2023)
Detail of female face on keystone. The faces on the upper levels were of women, influenced by Greek art. Like the keystones on the lower level, these are also each unique in their facial features and expressions. They mostly wear a floral crown and sport braided locks of hair on both sides.